2020
DOI: 10.21203/rs.3.rs-15405/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Probucol enhances the therapeutic efficiency of mesenchymal stem cells in the treatment of erectile dysfunction in diabetic rats by prolonging their survival time via Nrf2 pathway

Abstract: Background Intracavernous injection of mesenchymal stem cells (MSCs) is a promising method for Diabetic mellitus-induced erectile dysfunction (DMED), but short survival time of MSCs in cavernous is fatal defect for therapy. This study investigated therapeutic efficiency and potential mechanism of Probucol combined with MSCs. Methods In vivo study, total forty-eight 10-week-old male Sprague-Dawley (SD) rats were used in this study. Twelve rats received intraperitoneal injection of PBS as Sham Group; the rest re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Another previous study also showed that intra-cavernous transplantation of VEGF gene-modified bone marrow-derived MSCs resulted in improved erectile function in diabetic rats ( 20 ). The mechanism of this improvement may be via differentiating into endothelial cells and smooth muscle cells, and the secretion by these cells of many kinds of cytokines and other effects ( 21 , 22 ). In addition, another study also demonstrated that MSCs engineered to express stromal cell-derived factor 1 (SDF-1) have been shown to reduce erectile dysfunction in streptozotocin-induced diabetic rats by increasing levels of neuronal nitric oxide synthase (nNOS), VEGF, and growth factors ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another previous study also showed that intra-cavernous transplantation of VEGF gene-modified bone marrow-derived MSCs resulted in improved erectile function in diabetic rats ( 20 ). The mechanism of this improvement may be via differentiating into endothelial cells and smooth muscle cells, and the secretion by these cells of many kinds of cytokines and other effects ( 21 , 22 ). In addition, another study also demonstrated that MSCs engineered to express stromal cell-derived factor 1 (SDF-1) have been shown to reduce erectile dysfunction in streptozotocin-induced diabetic rats by increasing levels of neuronal nitric oxide synthase (nNOS), VEGF, and growth factors ( 23 ).…”
Section: Introductionmentioning
confidence: 99%